Free Media and Twitter in the 2016 Presidential Election: The Unconventional Campaign of Donald Trump. (August 2018) - Francia, Peter L.
This article examines the surprising outcome of the 2016 presidential election, which saw Donald Trump defy nearly all of the conventional wisdom to become the 45th president of the United States. Political commentators and experts offered several immediate postelection explanations for Trump's victory, one of which focused on how Trump was able to generate considerable unpaid or free media for himself, often directly through Twitter. This article explains the theory and rationale underlying the free media thesis (FMT) and then examines whether there is any preliminary empirical support for it. Using media tracking data and public opinion surveys, the results reveal that Trump indeed dominated the unpaid media market. Although the findings in this article cannot make causal claims about whether Trump's advantages in free media are the primary reason for his upset victory, the results, nonetheless, suggest that some of the basic conditions necessary for the FMT were present in the 2016 election and that the FMT offers a plausible avenue for further analysis and future research.